2009
DOI: 10.1002/cssc.200900167
|View full text |Cite
|
Sign up to set email alerts
|

Telomerization of Butadiene with Starch under Mild Conditions

Abstract: The design of industrial products based on bioresources is a challenging issue. Modification of starch, by hydrophobic chemical substituents, results in an innovative hydrophobic material. Herein, the hydrophobic part of the derivative, comprised of octadienyl chains, is introduced through catalytic butadiene telomerization. The process is efficiently conducted on starch in its granular form in an aqueous medium using hydrosoluble palladium complexes. After optimization, a turnover number (TON) of up to 550 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The other option is the use of co‐solvents, especially short‐chain alcohols. Once more, iso ‐propanol was shown to be a suitable phase‐mediating agent for the purpose of the telomerization of 1,3‐dienes with highly polar compounds in water, but in this case with Na 2 SO 4 added to maintain the physical properties of starch …”
Section: Nucleophilesmentioning
confidence: 99%
“…The other option is the use of co‐solvents, especially short‐chain alcohols. Once more, iso ‐propanol was shown to be a suitable phase‐mediating agent for the purpose of the telomerization of 1,3‐dienes with highly polar compounds in water, but in this case with Na 2 SO 4 added to maintain the physical properties of starch …”
Section: Nucleophilesmentioning
confidence: 99%
“…The solid was then filtered, washed with distilled water (2 9 100 mL) and dried to give a white powder (97 wt%/starting starch). DS (degree of substitution) was determined by NMR analysis and corresponded to the average number of substituted hydroxyl group/glucoside unit [4]. 1 …”
Section: Methodsmentioning
confidence: 99%
“…Among several homogeneous hydrosoluble catalysts, isolated [(p-allyl)Pd(TPPTS) 2 ]Cl catalyst was shown to be the most efficient in the telomerization of methanol in the presence of water as well as for the telomerization of starch in a water/iPrOH mixture [3]. The presence of a cosolvent in this reaction is essential to assure the solubility of butadiene in the medium and it was shown that the conversion decreased with the amount of organic co-solvent [4]. We studied the reaction in pure water but in the presence of surfactants to keep good contacts between the different constituents of the transformation.…”
Section: Introductionmentioning
confidence: 98%
“…Two major improvements were subsequently discovered: the addition of 12.5 wt% of sodium sulphate (Na 2 SO 4 ) stabilizes the starch sufficiently to allow reaction at 50 C without degradation [109]. Dimethyl isosorbide was used as an unconventional green co-solvent.…”
Section: Telomerization With Starchmentioning
confidence: 99%